IMPLEMENTASI METODE ECRITURE CRÉATIVE BERBASIS BUDAYA LOKAL UNTUK MENINGKATKAN KETERAMPILAN MENULIS BAHASA PERANCIS LEVEL B1 DELF - Sunendar, Dadang; Cahyani, Dwi; Mulyadi, Yadi (Universitas Pendidikan Indonesia, 2014)
This study aims to obtain data on: (1) a learning model in French writing in accordance with the demands of French writing skills of level B1 DELF CECRL developed from the implementation of local culture-based écriture creative method; and (2) the application of the Ecriture créative model in writing course of Production Ecrite regarding the acquisition of French writing skills of intermediate level (B1) DELF. The research method used in this study was Research and Development (R D) through: (1) preliminary studies, (2) planning and development models, and (3) validation of the model. Results indicate the local culture-based écriture créative model is able to help students improve their writing skills to the B1 DELF level with the rate of achievement of 63.33%. Based on the results, it can be said that this model proved effective in improving the learning process of students’ writing skills in the course of Production Ecrite V.